Effects of music-based group exercise in patients with acquired brain injury—a randomized controlled trial - Schrader, Mareike; Strank, Tobias; Sterr, Annette; Bamborschke, Stephan; Dohle, Christian (Frontiers in Psychology, 2026)
BackgroundCognitive impairment following acquired brain injury (ABI) is common. In this study, we investigated whether music-based group exercise (MBGE) is superior to standard therapy (ST) in improving cognitive deficits. In addition, motivational aspects were investigated. The trial has been registered with the German Register for Clinical Studies (DRKS00025566).MethodIn the experimental group of this randomized controlled trial, sensors were attached to conventional rehabilitation exercise equipment that used software (Jymmin®) to convert physical activity into good-sounding music. Three patients exercised at the same time and produced a piece of music together. The control group trained individually using the same machines, but without the music-producing sensors. The training schedule comprised four weeks, with three 30-min training session per week, respectively. The Montreal Cognitive Assessment, four subtests of the Test Battery for Attention, the Bayer Activities of Daily Living Scale, the Multidimensional Mood Questionnaire and a questionnaire on motivational aspects and preferred training constellation were carried out before (T1), after the intervention (T2) and 3 months later (T3).Results35 patients (MBGE: n = 17; ST: n = 18) completed the intervention and were included in the analysis. Both groups benefited from the exercise but no significant differences were found between the groups neither in the cognitive assessments, activities of daily living (ADL) nor mood. Group constellation was associated with greater enjoyment, whereas individual therapy was associated with subjectively perceived better concentration and more intensive training.DiscussionMBGE was not found to be superior to ST regarding cognition, ADL and mood. Both approaches demonstrated similar potential to positively influence these areas. Generally, individual preferences for group or single constellation should be considered. Further studies are needed to strengthen the evidence base for music-assisted therapy that addresses cognition and mood in people with ABI.Clinical trial registrationhttps://drks.de/search/de/trial/DRKS00025566, identifier DRKS00025566.